IMPLEMENTASI KEBIJAKAN PENANGANAN ANAK TIDAK SEKOLAH (ATS) DI DAERAH ISTIMEWA YOGYAKARTA: ANALISIS TANTANGAN DAN STRATEGI PENGUATAN AKSES PENDIDIKAN - Wahyu Insani; Suwadi; Frida Nurcahyani; Missa Serriawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Out-of-School Children (OTS) remains a challenge in efforts to achieve equal access to education in Indonesia. Although the government has stipulated Presidential Regulation of the Republic of Indonesia Number 3 of 2026 concerning the National Strategy for Handling Out-of-School Children, policy implementation at the regional level still faces various obstacles. This study aims to analyze the implementation of the policy for handling out-of-school children in the Special Region of Yogyakarta (DIY), identify the challenges faced, and examine strategies for strengthening access to education carried out by stakeholders. The study used a qualitative approach with a case study design. Data were obtained through a documentation study of transcripts of the coordination forum for handling out-of-school children in DIY involving the Education Office, Social Services Office, district/city governments, Family Hope Program (PKH) facilitators, and related stakeholders. Data were analyzed using thematic analysis with reference to George C. Edward III's policy implementation model, which includes dimensions of communication, resources, disposition, and bureaucratic structure. The results show that the implementation of the out-of-school children policy in DIY has been carried out through data collection, outreach, returning children to educational services, and mentoring mechanisms. However, implementation still faces challenges such as limited family finances, limited access to information, psychosocial factors, limited resources for facilitators, and issues with data integration and synchronization between agencies. Strategies to strengthen access to education are implemented through the development of People's Schools, optimization of the Family Hope Program, strengthening community education, providing non-formal education services, and strengthening cross-sector coordination. This study concludes that effective ATS management requires strengthening an integrated data system, increasing the capacity of facilitators, and strengthening communication and collaboration between stakeholders.